Adjoints and canonical forms of tree amplituhedra - Ranestad, Kristian; Sinn, Rainer; Telen, Simon (MATHEMATICA SCANDINAVICA, 2024)
We consider semi-algebraic subsets of the Grassmannian of lines in three-space called tree amplituhedra. These arise in the study of scattering amplitudes from particle physics. Our main result states that tree amplituhedra in $Gr(2,4)$ are positive geometries. The numerator of their canonical form plays the role of the adjoint in Wachspress geometry, and is uniquely determined by explicit interpolation conditions.